2014
DOI: 10.1037/a0035712
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in methadone maintenance patients: Effects of time relative to dosing and maintenance dose level.

Abstract: Given the long-term nature of methadone maintenance treatment, it is important to assess the extent of cognitive side effects. This study investigated cognitive and psychomotor performance in fifty-one methadone maintenance patients (MMP) as a function of time since last methadone dose and maintenance dose level. MMP maintained on doses ranging from 40 to 200 mg (Mean = 97 mg) completed a battery of psychomotor and cognitive measures across two sessions, during peak and trough states, in a double-blind crossov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 51 publications
(79 reference statements)
1
27
0
1
Order By: Relevance
“…Specifically, one may claim that the impaired performance of the methadone maintenance patients is due to timing of methadone administration. Rass et al (2014) have found that methadone negatively affects physiological and cognitive functioning. These effects are evident 1 h after dose administration and reach peak at approximately 2 h post dose.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, one may claim that the impaired performance of the methadone maintenance patients is due to timing of methadone administration. Rass et al (2014) have found that methadone negatively affects physiological and cognitive functioning. These effects are evident 1 h after dose administration and reach peak at approximately 2 h post dose.…”
Section: Discussionmentioning
confidence: 98%
“…For example, methadone, which has been widely prescribed for opioid users, can have both positive and negative outcomes (Rass et al, 2014). …”
Section: Neurocognitive Approach To Pe: Contentmentioning
confidence: 99%
“…The cells exposed to methadone exhibited some changes, including high permeability of the mitochondrial outer membrane and transfer of BAX into mitochondria, which also lead to the release of cytochrome C . A study on mitochondria of methadone‐treated rat livers showed that methadone causes mitochondrial uncoupling and also has ion transferability, so it induces cell death due to its ability to significantly decrease cellular ATP levels . Increasing the production of reactive oxygen species, as well as increasing calcium, plays an important role in inducing the cell death.…”
Section: Introductionmentioning
confidence: 99%